Cardiosurgical endovascular intervention during pregnancy - S. O. Siromakha; Yu. V. Davydova; A. Yu. Limanska; B. V. Cherpak; V. V. Lazoryshynets (Клінічна хірургія, 2020)
Objective. To share the experience of endovascular interventions in pregnant women and women in labor, gained by national team “obstetric cardiology”.